Disney Frozen: Challenging the Traditional Gender Roles of Disney Princesses - Putri, Novia Ardellia (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
Society's expectations of how we should act, speak, dress, take care of ourselves, and behave are known as gender roles. For instance, it is expected of girls and women in general to behave politely, be accommodating, and be caring. Men are typically thought to be powerful, aggressive, and brave. Gender expectations exist in every civilization, ethnic group, and culture, albeit they might differ greatly from group to group. They might alter over time even within the same society The 3D computer-animated musical fantasy movie Frozen was created in the United States and distributed by Walt Disney Pictures. The Hans Christian Andersen fairy tale "The Snow Queen" served as the basis for this 53rd Disney animated feature film. tells the tale of a brave princess named Anna who sets out to locate her estranged sister Elsa, whose ice abilities unintentionally plunged their kingdom into an endless winter, along with a gruff iceman, devoted reindeer, and gullible snowman. By utilizing the idea of the three waves of feminism, this study tries to understand how Disney's Frozen challenges both the established gender roles of Disney Princesses and the society's perception of those of the main female characters. The study's findings demonstrate that Disney's difficulties are evident in their two primary female characters, who differ from the previous Disney Princesses. The way the society reacted to the Princess characters' differences was also depicted in the movie.